RELASI SINTAGMATIK MITOS DAN RITUAL DAYAK MAANYAN PAJU SEPULUH SYNTAGMATIC RELATIONS OF MYTHS AND RITUAL OF THE DAYAK MAANYAN PAJU SEPULUH - Albertus Purwaka; Paul Diman; Isti Prihatini (FKIP, Universitas Palangka Raya, 2023)
Myth and ritual are understood as two things that cannot be separated from one another. The relationship between the two can be transformed in the form of positional relations which show a network of relations between figures and events, domains and characters in a model. Given the importance of myths and rituals in forming the structure of the mind of the Ma'anyan Dayak tribe, it is interesting to present an analysis with regard to syntagmatic and paradigmatic relations in the Ma'anyan Dayak traditional marriage ceremony. The purpose of this study was to gain knowledge about myths, the meaning of myths, and their relation to rituals performed by the Maanyan Paju Ten Dayak community. The data collection technique was carried out by hermeneutic reading. Data analysis was carried out by structural analysis, semiotic analysis and content analysis guided by the Levi-Struss structural approach strategy. The results of the analysis of syntagmatic and paradigmatic relations show that myth in naliwakas is a Ma'anyan human dialectic with social reality that contains the framework of a religious system which in the past or present has been or is being applied as religious truth. The rituals that are performed basically represent the arrangement of symbols that are objectified in myths. On the other hand, ceremonies in the Maanyan Dayak community are associated with magical acts and the cult of the ancestors as religious acts. Rituals that reveal historical and social relations by referring to mystical notions within the framework of constitutive rituals, in this way the traditional wedding ceremony becomes distinctive. Furthermore, the meaning associated with this relationship is nothing but purification and protection which is called factive ritual.